2017
DOI: 10.1038/cddis.2017.422
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib promotes autophagy and apoptosis through VEGFR2/STAT3/BCL-2 signaling in osteosarcoma

Abstract: The cure rate of osteosarcoma has not improved in the past 30 years. The search for new treatments and drugs is urgently needed. Apatinib is a high selectivity inhibitor of vascular endothelial growth factor receptor-2 (VEGFR2) tyrosine kinase, exerting promising antitumoral effect in various tumors. The antitumor effect of Apatinib in human osteosarcoma has never been reported. We investigated the effects of Apatinib in osteosarcoma in vitro and in vivo. Osteosarcoma patients with high levels of VEGFR2 have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
181
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(199 citation statements)
references
References 44 publications
15
181
2
1
Order By: Relevance
“…In tumor cells, autophagy plays a dual role as it can promote death or survival. Some studies have confirmed that TKI resistance is associated with increased autophagic activity (23)(24)(25). In this report, we found that apatinib induced autophagy in PTC, as it does in other types of tumors.…”
Section: Discussionsupporting
confidence: 79%
“…In tumor cells, autophagy plays a dual role as it can promote death or survival. Some studies have confirmed that TKI resistance is associated with increased autophagic activity (23)(24)(25). In this report, we found that apatinib induced autophagy in PTC, as it does in other types of tumors.…”
Section: Discussionsupporting
confidence: 79%
“…Kaplan-Meier survival analysis revealed that high KDR immunoreactivity was predictive of unfavorable outcome in this cohort ( Figure 5B-D), suggesting a potential role for this protein in osteosarcoma progression. Underscoring our findings, a KDR inhibitor, Apatinib, has been shown to repress the growth of osteosarcoma in vivo [59].…”
Section: Kdr Is Recurrently Amplified Highly Expressed and Associatesupporting
confidence: 74%
“…Besides, there is ample evidence indicating that cellular metabolic disorders may be associated with drug resistance during cancer therapy [36,37]. Apatinib has also been found to promote autophagy and apoptosis through the VEGFR2 signal transducer and activator of transcription 3 (STAT3)/B cell lymphoma 2 (BCL2) signaling pathway in osteosarcoma, and it has been found that a combined use of autophagy inhibitors can enhance the anti-tumor effects of apatinib [38]. Similarly, it has been shown that in colorectal cancer inhibition of autophagy can boost its efficacy, both in vitro and in vivo [39].…”
Section: Discussionmentioning
confidence: 99%